Semi-active radar systems for critical facilities monitoring and protection - A. V. Barkhatov; V. I. Veremjev; A. A. Golovkov; V. M. Kutuzov; V. N. Malyshev; O. G. Petkau; N. S. Stenjukov; M. S. Shmyrin (Известия высших учебных заведений России: Радиоэлектроника, 2015)
The principles of constru.ction and implementation of semi-active radar systems, using the illumination from third-party sources are presented. The results of theoretical and experimental researches of the Saint-Petersburg state electrotechnical university "LETI" n. a. V. I. Ulyanov (Lenin) and JSC «SRI "Vector"» in this direction are given. The advantages of semi-active radar systems, the possibility of coherent processing with a large accumulation time in com.bination with the digital formation of the directional diagrams of the receiving antenna arrays, as well as prospects of application systems semi-active radar for the protection of important sites and monitoring areas, including the detection and orbital support of ground, surface and aerial objects. The stru.cture of the developed passive coherent radar com.plex is described; its basic technical characteristics are given.